Deletion of cyclin dependent kinase inhibitor 2a gene as a marker of oropharyngeal carcinomas non-associated with human papillomavirus and its prognostic value - I.S. Shponka; Bondarenko O.O. Bondarenko ч; O.V. Kovtunenko; V.V. Rakhmanov (Medičnì Perspektivi)
Patients with human papilloma virus associated oropharyngeal squamous cell carcinoma generally have better treatment outcomes and prognosis compared to those with non-papillomavirus-associated oropharyngeal squamous cell carcinoma. However, prognostic evaluation for non-papillomavirus-associated oropharyngeal squamous cell carcinoma remains a problem that could be solved through the molecular mechanisms of squamous cell carcinoma for the purpose of further development of target therapies. Detection of cyclin dependent kinase inhibitor 2a gene deletion in oropharyngeal squamous cell carcinomas can have clinical significance as it may serve as a prognostic marker and potentially guide treatment decisions. To investigate and analyze cyclin dependent kinase inhibitor 2a gene alterations in oropharyngeal squamous cell carcinoma comparing with clinical data (age of the patient, TNM stage), their histological features and occurrence of papillomavirus infection markers (p16 expression). Formalin-fixed and paraffin-embedded samples after transoral radical surgery of oropharyngeal tumors from 26 male patients with average age 57.35±10.33 years were studied. Histological, immunohistochemical analyses and fluorescent in-situ hybridization were performed to assess histological features, p16 expression, and cyclin dependent kinase inhibitor 2a gene gene abnormalities respectively. Homozygous deletion of cyclin dependent kinase inhibitor 2a gene was statistically analyzed and compared with p16 expression, age, and occurrence of nodal metastases in investigated patients. Our study demonstrated that the patients with non-papillomavirus-oropharyngeal squamous cell carcinoma with cyclin dependent kinase inhibitor 2a gene homozygous deletion had the highest risk of the nodal metastases development. Our findings suggest that not only detection of the loss of p16 expression, but also the evaluation of homozygous cyclin dependent kinase inhibitor 2a gene deletion might be predictive of worse outcome specifically in oropharyngeal squamous cell carcinomas.